2011
DOI: 10.3390/ijerph8062090
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expression by Low-Dose Arsenic Exposure in Humans and Cultured Cardiomyocytes: Assessment by Real-Time PCR Arrays

Abstract: Chronic arsenic exposure results in higher risk of skin, lung, and bladder cancer, as well as cardiovascular disease and diabetes. The purpose of this study was to investigate the effects on expression of selected genes in the blood lymphocytes from 159 people exposed chronically to arsenic in their drinking water using a novel RT-PCR TaqMan low-density array (TLDA). We found that expression of tumor necrosis factor-α (TNF-α), which activates both inflammation and NF-κB-dependent survival pathways, was strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
(64 reference statements)
0
26
0
Order By: Relevance
“…It has been suggested that arsenic alters common pathways such as those involved in oxidative stress and inflammatory signaling, which underlie a variety of arsenic-associated diseases (States et al 2009, Straif et al 2009, Mo et al 2011, Kim et al 2015). The generation of ROS in particular is a major pathological mechanism induced by arsenic and is involved in the pathogenesis of cancer (Shi et al 2004), insulin resistance (Padmaja Divya et al 2015), metabolic syndrome (Ando et al 2009), and cardiovascular disease (States et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that arsenic alters common pathways such as those involved in oxidative stress and inflammatory signaling, which underlie a variety of arsenic-associated diseases (States et al 2009, Straif et al 2009, Mo et al 2011, Kim et al 2015). The generation of ROS in particular is a major pathological mechanism induced by arsenic and is involved in the pathogenesis of cancer (Shi et al 2004), insulin resistance (Padmaja Divya et al 2015), metabolic syndrome (Ando et al 2009), and cardiovascular disease (States et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mo et al found that DNMT1 expression was upregulated by low-dose arsenic exposure in a human cardiomyocyte cell line (Mo et al, 2011). Cui et al reported that exposure to low levels of arsenic reduced DNMT1 expression and inhibited DNMT activity in human liver cancer cells (Cui et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a human cardiomyocyte cell line, exposure to low-dose arsenic induced changes in DNA methyltransferase 1 (DNMT1) gene expression (Mo et al, 2011). Long-term exposure to low-dose arsenic altered mRNA and protein levels of DNMT1 and DNMT3A in human urothelial cells compared with the levels in human urothelial cells that were not exposed to arsenic .…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study [46] further demonstrated that expression of ERCC1 was decreased at both the mRNA and protein levels. A dosedependent decrease in the mRNA expression of ERCC1 was also found in human cardiomyocytes exposed to arsenite for 72 h [47]. However, elevated ERCC1 gene expression has The cells were lysed and DNA extracted for analysis of the BPDE-DNA adducts.…”
Section: Possible Mechanisms Of Ner Inhibition By Arsenic 41 Arsenicmentioning
confidence: 94%